Involvement of the SIRT1/PGC-1α Signaling Pathway in Noise-Induced Hidden Hearing Loss - Liu, Yu-Hui; Jiang, Yi-Hong; Li, Cong-Cong; Chen, Xue-Min; Huang, Li-Gui; Zhang, Min; Ruan, Bai; Wang, Xiao-Cheng (Frontiers in Physiology, 2022)
Objective: To establish an animal model of noise-induced hidden hearing loss (NIHHL), evaluate the dynamic changes in cochlear ribbon synapses and cochlear hair cell morphology, and observe the involvement of the SIRT1/PGC-1α signaling pathway in NIHHL. Methods: Male guinea pigs were randomly divided into three groups: control group, noise exposure group, and resveratrol treatment group. Each group was divided into five subgroups: the control group and 1 day, 1 week, 2 weeks, and 1 month post noise exposure groups. The experimental groups received noise stimulation at 105 dB SPL for 2 h. Hearing levels were examined by auditory brainstem response (ABR). Ribbon synapses were evaluated by inner ear basilar membrane preparation and immunofluorescence. The cochlear morphology was observed using scanning electron microscopy. Western blotting analysis and immunofluorescence was performed to assess the change of SIRT1/PGC-1α signaling. Levels of superoxide dismutase (SOD), malondialdehyde (MDA), catalase (CAT), ATP and SIRT1 activity were measured using commercial testing kits. Results: In the noise exposure group, hearing threshold exhibited a temporary threshold shift (TTS), and amplitude of ABR wave I decreased irreversibly. Ribbon synapse density decreased after noise exposure, and the stereocilia were chaotic and then returned to normal. The expression and activity of SIRT1 and PGC-1α protein was lower than that in the control group. SOD, CAT and ATP were also influenced by noise exposure and were lower than those in the control group, but MDA showed no statistical differences compared with the control group. After resveratrol treatment, SIRT1 expression and activity showed a significant increase after noise exposure, compared with the noise exposure group. In parallel, the PGC-1α and antioxidant proteins were also significantly altered after noise exposure, compared with the noise exposure group. The damage to the ribbon synapses and the stereocilia were attenuated by resveratrol as well. More importantly, the auditory function, especially ABR wave I amplitudes, was also promoted in the resveratrol treatment group. Conclusion: The SIRT1/PGC-1α signaling pathway and oxidative stress are involved in the pathogenesis of NIHHL and could be potential therapeutical targets in the future.